2021
DOI: 10.3390/ijerph18042075
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of a Telerehabilitation Program Based on Aerobic Exercise in Women with Fibromyalgia

Abstract: Background: We analyzed the immediate effects of a Telerehabilitation Program (TP) based on aerobic exercise in women with fibromyalgia (FM) syndrome during the lockdown declared in Spain due to the COVID-19 pandemic. Methods: A single-blind randomized controlled trial was designed. Thirty-four women with FM were randomized into two groups: TP group and Control group. The intervention lasted 15 weeks, with 2 sessions per week. The TP based on aerobic exercise was guided by video and the intensity of each sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 57 publications
1
66
0
9
Order By: Relevance
“…The study demonstrated that the efficacy of the therapist-monitored interactive telerehabilitation system was similar to that of conventional therapist-delivered face-to-face therapy to improve balance in those with chronic stroke [ 33 ]. Another example of home-based telerehabilitation for chronic conditions is the study by Hernando-Garijo et al [ 34 ], a randomized controlled clinical trial investigating video-based aerobic exercise in women with fibromyalgia during the lockdown caused by the COVID-19 pandemic. The results showed that the intervention group achieved statistically significant improvements in pain intensity, mechanical pain sensitivity and psychological distress compared to a control group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that the efficacy of the therapist-monitored interactive telerehabilitation system was similar to that of conventional therapist-delivered face-to-face therapy to improve balance in those with chronic stroke [ 33 ]. Another example of home-based telerehabilitation for chronic conditions is the study by Hernando-Garijo et al [ 34 ], a randomized controlled clinical trial investigating video-based aerobic exercise in women with fibromyalgia during the lockdown caused by the COVID-19 pandemic. The results showed that the intervention group achieved statistically significant improvements in pain intensity, mechanical pain sensitivity and psychological distress compared to a control group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another example of home-based telerehabilitation for chronic conditions is the study by Hernando-Garijo et al [ 34 ], a randomized controlled clinical trial investigating video-based aerobic exercise in women with fibromyalgia during the lockdown caused by the COVID-19 pandemic. The results showed that the intervention group achieved statistically significant improvements in pain intensity, mechanical pain sensitivity and psychological distress compared to a control group [ 34 ]. Telerehabilitation has also been used to support home-based exercises following hip surgery in the elderly, where exercises were delivered by caregivers at home instead of a health professional and guided by video recordings [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the 749 studies initially detected, a total of 41 RCTs were included [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. The PRISMA 2020 flow chart is detailed in Appendix A.2 .…”
Section: Resultsmentioning
confidence: 99%
“…Home-based aerobic conditioning has also been found to induce physiological and psychological benefits in patients with FM, including improvements in pain [ 69 ]. Relatedly, in a recent small (i.e., 17 individuals per arm) clinical trial conducted in Spanish patients with FM also during the COVID-19 lockdown [ 47 ], an intensive 15-week (2 sessions/week) telerehabilitation program based on aerobic exercise showed positive effects on pain intensity, functional impairment and psychological distress compared to a passive control group. On the other hand, CBT has been proven to be also efficacious (with small-to-medium effect sizes) for improving pain, health-related quality of life, negative mood, disability and fatigue in patients with FM [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar virtual approaches (e.g., using videos) have also been used by other health centers in Spain in the search of the benefit of patients with FM under quarantine. In this regard, Hernando-Garijo and colleagues [ 47 ] made available a home-based intervention of aerobic exercise during lockdown, finding, in a small sample size, RCT- positive results in pain intensity, functional impairment, pain catastrophizing and emotional distress compared to a passive control group. To date, as far as we know, no study has evaluated the efficacy of a virtual multicomponent treatment for FM in general or during the pandemic outbreak specifically.…”
Section: Introductionmentioning
confidence: 99%